Fermentation and Anaerobic Oxidation of Organic Carbon in the Oxygen Minimum Zone of the Upwelling Ecosystem Off Concepción, in Central Chile - Srain, Benjamín M.; Sobarzo, Marcus; Daneri, Giovanni; González, Humberto E.; Testa, Giovanni; Farías, Laura; Schwarz, Alex; Pérez, Norma; Pantoja-Gutiérrez, Silvio (Frontiers in Marine Science, 2020)
We studied dynamic of fermentation and anaerobic degradation of organic matter in the Oxygen Minimum Zone (OMZ) of the Humboldt Current System by analyzing products of main anaerobic microbial reactions (fermentation, denitrification, and reduction of Fe(III)s and SO42-) during laboratory incubations of OMZ waters and in the water column during a year cycle. Fermentation of glucose and amino acids resulted in production of volatile fatty acids, mainly acetate, that were detected year-round and associated to high primary production rates, dissolved organic carbon (DOC) increase, and presence of Equatorial Sub Surface anoxic waters at the sampling site off Concepción in central Chile. While ethanol was produced from glucose fermentation by OMZ water microbes, it was not detected in the water column. Ammonium produced by fermentation of amino acids during anoxic represents a source of NH4+ that could explain previously unaccounted for NH4+ requirements for anammox bacteria and microaerophilic NH4+ oxidizer Thaumarchaeota in anoxic marine ecosystems. Evidence of thermodynamically feasible acetate oxidation with Fe(III)s as electron acceptor unveils microbial ability to reduce solid-phase iron carried by rivers using fermented metabolites in oxygen-depleted water, thus releasing dissolved bioavailable Fe. We evidenced that products of fermentation are advected to oxygenated waters of Sub Antarctic origin during austral winter intrusion and potentially supplying C, N and electron sources, a process likely to be enhanced due to both thermodynamically (temperature) and kinetic (organic load) decrease in O2 during the XXI century.